2015
DOI: 10.1021/acs.jpcc.5b05095
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the Origins of Panchromatic Spectra in Squaraine Thin Films Targeted for Organic Photovoltaic Devices

Abstract: Squaraines offer significant potential for organic photovoltaics because of their broad absorbance and high extinction coefficients as well as their expected use as mechanistic probes in such devices. In this work steps are taken to develop a comprehensive understanding of the excited state properties of squaraines, based on their molecular structure and the resulting solid state packing. Accurate assignments of the absorption spectral peaks are made based on an essential states model, expanded to include inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
153
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(165 citation statements)
references
References 47 publications
(158 reference statements)
11
153
1
Order By: Relevance
“…Comparing our research results with those obtained in [22][23][24][25], which correspond to the near UV, visible and deep IC region of electromagnetic field, one can conclude good agreement for resonant absorption, which could be attributed and explained with spatial and boundary conditions, i.e. with effect of quantum confinement and nanoscale dimensions of structures, exciton coupling and overall dynamic of excitons.…”
Section: Ultrathin Films Permittivitysupporting
confidence: 78%
See 1 more Smart Citation
“…Comparing our research results with those obtained in [22][23][24][25], which correspond to the near UV, visible and deep IC region of electromagnetic field, one can conclude good agreement for resonant absorption, which could be attributed and explained with spatial and boundary conditions, i.e. with effect of quantum confinement and nanoscale dimensions of structures, exciton coupling and overall dynamic of excitons.…”
Section: Ultrathin Films Permittivitysupporting
confidence: 78%
“…New nanomaterial -squaraines -has been introduced [24] which offers significant potential for organic photovoltaic devices due to their broad absorbance and high extinction coefficients as well as their expected usage as mechanic probes in such devices. In this work are taken all necessary steps to develop a comprehensive understanding of the excited-state properties of squaraines based on their molecular structure and the resulting solid-state packing.…”
Section: Ultrathin Films Permittivitymentioning
confidence: 99%
“…However, such an interpretation is inconsistent with the single crystal structure of DHSQ(OH) 2 which exhibits a single molecule per unit cell with the conjugated backbones (and transition dipole moments) parallel to one another throughout the crystal [27]. Rather, in a previous study concerning a series of similar SQs with linear side chains, we demonstrated through a validated computational approach that the origin of the "double-hump" film absorption results from intermolecular charge transfer (ICT) between neighboring molecules in slip stacked SQ aggregates [28]. In a simplified picture, the double hump arises due to coupling between a charge separated state, which carries little oscillator strength, and the optically allowed local excitation, which carries the bulk of oscillator strength.…”
Section: Dhsq(oh) 2 Aggregatementioning
confidence: 89%
“…It is the packing and morphology of the squaraines that leads to this broadening but, with multiple excited states accessible through crystallization, some aggregates may actually inhibit device performance because of energy level mismatch [20]. In fact, in recent work there has been significant confusion regarding the assignment of the excited states [21][22][23][24][25][26][27], with low energy absorption features typically being assigned to J-aggregates despite no observable fluorescence nor a crystal structure that would support Davydov splitting [28]. Despite an excellent description of the structure-property relationship in anilinic squaraines by Brück et al [27], we consider the excited states assignment to restrict future progress and we seek to fully correct that assignment herein.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report how these properties can be controlled through choice of structure and process route [6][7][8][9] . Some authors have addressed the broadening of spectral response using panchromatic absorbers 10 or ternary systems 11 . Absorption spectra have been analysed in terms of the relationship between spectral shape and chemical structure or conformation [12][13][14] , and individual molecules 15 or monomers 16 with high optical extinction have been presented.…”
Section: Introductionmentioning
confidence: 99%